Ablation resistance properties and microstructure of plasma spraying coatings - LIN Bingtao; ZHANG Baohong; TANG Liangliang; XIONG Ning; ZHANG Danhua; ZHANG Lei (Fenmo yejin jishu)
Tungsten (W) and tungsten alloy coatings were prepared by plasma spraying on 45# steel and TC4 titanium alloys. Ablation tests were carried out under the different ablation conditions. The ablation resistance of the coatings was compared, and the ablation failure mechanism of the coatings was discussed. The results show that, the ablation resistance of the base materials is improved by spraying W coatings. When the ablation temperature is 2600 ℃ for 11 s, the coatings are oxidized, and there is no ablation phenomenon. When the ablation temperature is 3400 ℃ for 6 s, the coatings have the obvious ablation, indicating that the heat is transferred to the matrix, resulting in the matrix temperature exceeding the own melting point. The W+Al2O3 and W+ZrO2 composite coatings slow down the heat transfer rate from the coating surface to the substrate, and improve the ablative resistance of the substrate materials. The dynamometer curves of W+Al2O3 and W+ZrO2 composite coatings show the zigzag decline and do not resist the erosion, but the coating ablative resistance time is relatively long.